Lipid levels achieved after a first myocardial infarction and the prediction of recurrent atherosclerotic cardiovascular disease. (1st December 2019) - Ohm, Joel; Hjemdahl, Paul; Skoglund, Per H.; Discacciati, Andrea; Sundström, Johan; Hambraeus, Kristina; Jernberg, Tomas; Svensson, Per
Abstract: Background: Low density lipoprotein cholesterol (LDL-C) goals post-myocardial infarction (MI) are debated, and the significance of achieved blood lipid levels for predicting a first recurrent atherosclerotic cardiovascular disease (rASCVD) event post-MI is unclear. Methods: This was a cohort study on first-ever MI survivors aged ≤76 years attending 4–14 week revisits throughout Sweden 2005–2013. Personal-level data was collected from SWEDEHEART and linked national registries. Exposures were quintiles of LDL-C, high density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TGs) at the revisit. Group level associations with rASCVD (nonfatal MI or coronary heart disease death or fatal or nonfatal ischemic stroke) were estimated in Cox regression models. Predictive capacity was estimated by differences in C-statistic, integrated discriminatory improvement, and net reclassification improvement when adding each blood lipid to a validated risk prediction model. Results: 25, 643 patients, 96.9% on statin therapy, were followed during a mean of 4.1 years. rASCVD occurred in 2173 patients (8.5%). For LDL-C and TC, moderate associations with rASCVD were observed only in the 5th vs. the lowest (referent) quintiles. For TGs and HDL-C increased risks were observed in quintiles 3–5 vs. the lowest. Minor predictive improvements were observed when lipid fractions were added to the risk model but the discrimination overall was poor (C-statistics <0.6). Conclusions: Our data question the importance of LDL-C levels achieved at first revisit post-MI for decisions on continued treatment intensity considering the weak association with rASCVD observed in this post-MI cohort. Highlights: After a first myocardial infarction (MI) the annual recurrence of MI or stroke was 2%. 96.9% of the 25, 643 patients were on statin therapy at study baseline. Blood lipid levels were poorly predictive of a recurrent MI or stroke. Associations with recurrence were weakest for LDL-C and strongest for triglycerides.